1994
DOI: 10.1007/bf02388567
|View full text |Cite
|
Sign up to set email alerts
|

A re-evaluation of the tissue distribution and physiology of xanthine oxidoreductase

Abstract: Xanthine oxidoreductase is an enzyme which has the unusual property that it can exist in a dehydrogenase form which uses NAD+ and an oxidase form which uses oxygen as electron acceptor. Both forms have a high affinity for hypoxanthine and xanthine as substrates. In addition, conversion of one form to the other may occur under different conditions. The exact function of the enzyme is still unknown but it seems to play a role in purine catabolism, detoxification of xenobiotics and antioxidant capacity by produci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(11 citation statements)
references
References 291 publications
0
10
0
1
Order By: Relevance
“…First, xanthine oxidase activity is not likely to be the source of ROS in both liver and small intestine because neither allopurinol nor hypox- anthine resulted in a detectable effect. Moreover, the granular form of final reaction product was not indicative of a soluble enzyme, such as xanthine oxidase (Kooij, 1994). Secondly, the presence of NADP did not have any effect.…”
Section: Discussionmentioning
confidence: 87%
“…First, xanthine oxidase activity is not likely to be the source of ROS in both liver and small intestine because neither allopurinol nor hypox- anthine resulted in a detectable effect. Moreover, the granular form of final reaction product was not indicative of a soluble enzyme, such as xanthine oxidase (Kooij, 1994). Secondly, the presence of NADP did not have any effect.…”
Section: Discussionmentioning
confidence: 87%
“…There are several extra-mitochondrial sources of ROS and the assignment of the mitochondria as the site of ROS generation is not completely resolved. [29][30][31] We demonstrated that PKAcat induced ROS generation and Trolox inhibited PKAcat-induced ROS generation. Furthermore, PKAcatinduced ∆ m depolarization was also inhibited by another ROS scavenger, N-acetylcysteine (NAC; 400 mol/L, data not shown).…”
Section: Pkacat-induced Ros Generation In Mitochondriamentioning
confidence: 78%
“…The hepatic localization of XOR is zonally distributed, with higher activity in pericentral, compared with periportal, hepatocytes (44). The zonal distribution of XOR corresponds to regions where ischemia and hypoxia would be most severe, as oxygen is extracted as blood flows from the portal triad to the central vein branches.…”
Section: Discussionmentioning
confidence: 99%